Manifesto for an international digital mental health network. Issue 1 (1st January 2019) - Maron, Eduard; Baldwin, David S.; Balõtšev, Roman; Fabbri, Chiara; Gaur, Vikas; Hidalgo-Mazzei, Diego; Hood, Sean; Juhola, Martti; Kampman, Olli; Kasper, Siegfried; Kärkkäinen, Hilkka; Látalová, Klára; et al.
Abstract: Current mental health services across the world remain expert-centric and are based on traditional workflows, mostly using impractical and ineffective electronic record systems or even paper-based documentation. The international network for digital mental health (IDMHN) is comprised of top-level clinicians, regulatory and ICT experts, genetic scientists, and support organizations. The IDMHN has been formed to enable the implementation of digital innovations in clinical practice, hereby facilitating the transformation of current mental health services to be more personalized and more responsive to patients and healthcare needs. This consensus statement summarizes the consortium's vision and strategy for further development of digital mental health.